Effects of spirulina as a functional ingredient in arsenic-induced broiler diet on growth performance and hematobiochemical parameters - Talha, Md Mowdudul Hasan; Hossain, Md Anwar; Aktaruzzaman, Md; Islam, Md Siddiqul; Khasnobish, Akash; Akanda, Md Rashedunnabi (Journal of Advanced Veterinary and Animal Research, 2022)
Objectives: The purpose of this research was to look into the impacts after the implication of feeding broiler chickens with spirulina in arsenic-incited toxicities. Materials and Methods: Birds (n = 125) were distributed equally (n = 25) into four groups treated (T1, T2, T3, T4) and a group controlled, T0 (normal feed and water without supplement), the group taking in arsenic trioxide (100 mg/l)-induced diet (T1), and the groups T2, T3, and T4 (feed supplemented with 50, 100, and 200 mg/l of spirulina along with Arsenic Trioxide, respectively). The body weight and hematobiochemical parameters were recorded every 7 days. Results: Different growth development indicators, e.g., body weight, feed intake ratio, feed conversion ratio, depression, and skin lesions, were weak in arsenic trioxide groups and upstanding in the arsenic plus spirulina group. Over and above, the lack of body weight gain in chicken (2.7%–13.00%) in the arsenic-introduced groups given spirulina (T2, T3, and T4) overtook the mere groups exposed to arsenic, where the lack of weight gain was optimum (54.90%). Thereafter, in arsenic-instituted groups given spirulina (T2, T3, and T4), the drop in total erythrocyte count, total leukocyte count, hemoglobin, and packed cell volume values became less notable than in arsenic pollutant groups (T1, p < 0.01). Two measurable factors (serum glutamate pyruvate transaminase and serum glutamic oxaloacetic transaminase) were substantially (p < 0.01) raised in the group (T1) treated with arsenic, but in the arsenic-induced groups (T2, T3, and T4) treated with spirulina, they were elevated less. Conclusion: This study demonstrates that arsenic is a threat to poultry. However, spirulina may be advantageous for alleviating the effects of arsenic in poultry. J. Adv. Vet. Anim. Res., 9(3): 501–508, September 2022 http://doi.org/10.5455/javar.2022.i619